A179: Improving Pneumococcal Vaccination Rate in the Pediatric Rheumatology Clinic. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Harris, Julia G.; Maletta, Kristyn I.; Ren, Bixiang; Olson, Judyann C.
Abstract : Background/Purpose: This quality improvement project was conducted to increase pneumococcal vaccination rates in eligible Pediatric Rheumatology Clinic patients. Streptococcus pneumoniae is a leading cause of bacteremia, meningitis, pneumonia, sinusitis, and acute otitis media. Many patients in the Pediatric Rheumatology Clinic are at increased risk of pneumococcal disease secondary to a deficient immune system and/or immunosuppressive medications. Infections remain one of the leading causes of hospitalization and death in patients with certain rheumatic diseases. The Centers for Disease Control and Prevention recommends both the 13‐valent pneumococcal conjugate vaccine (PCV13) and the 23‐valent pneumococcal polysaccharide vaccine (PPSV23) for this high‐risk population. Methods: Baseline immunization rates were assessed for eligible clinic patients over a four week period. Eligible patients include children at least two years old and adults with systemic lupus erythematosus and patients currently on or starting an immunosuppressive medication. Interventions included a presentation to rheumatology providers and nurses, creation of clinic document with immunization algorithm, previsit planning, placing reminders on patient clinic forms, and sending letters to out‐of‐state patients. Chart reviews of eligible patients occurred throughout the study period. Control charts were established to portray change in immunization rate. Results: The pre‐intervention immunization rate for 90 eligible Pediatric Rheumatology Clinic patients was 6.7% for PCV13, 8.9% for PPSV23, and 0% for both vaccines. Data from 53 weeks were analyzed following the interventions for a total of 1123 eligible patient visits and 306 separate patients. The average post‐intervention immunization rate was 48.4% for PCV13, 28.4% for PPSV23, and 23.3% for both vaccines. These rates are statistically higher than the pre‐intervention rates (all p < 0.001). There was an increase in immunization rates following each major intervention. Conclusion: Pneumococcal vaccination is an important part of the care for systemic lupus erythematosus patients and pediatric rheumatology patients on immunosuppressive medications. Simple interventions through this quality improvement project led to a marked increase in pneumococcal vaccination rates in this vulnerable population.